Contribution of Social Media Addiction on Ethics for Communicating Students to Lecturers - Rista Sandra Ritonga; Agung Tri Prasetia (Indonesian Journal of Counseling and Development, 2019)
Social media has now become one of the needs of teenagers. Addiction to social media in adolescents especially students can influence social life, especially in terms of communication either directly or through short messages. In life in the world of universities, students are never free to communicate with lecturers. Most students who are infected with social media addiction send a short message to the Lecturer as well as how he sent a short message to his friend on social media. This research aims to see how much the contribution of social media addiction to the communication ethics of students to lecturers is given. The sample in this study was specifically given to students using random sampling. The instrument used in this study was social media addiction and communication ethics. The significance of the contribution of social media addiction to the ethics of communicating students to lecturers is at a moderate level